Social prescribing for people with mental health needs living in disadvantaged communities: the Life Rooms model - Shaima M. Hassan; Clarissa Giebel; Esmaeil Khedmati Morasae; Clare Rotheram; Virginia Mathieson; Daniel Ward; Vicky Reynolds; Alan Price; Katie Bristow; Cecil Kullu (BMC, 2020)
Abstract Background People live socially complex lives and have different health care needs influenced by socio-economic factors such as deprivation, unemployment, and poor housing. Lack of access to community based social care results in people seeking social support from health care services. This study explores the Life Rooms as a social prescribing model addressing the social determinants of mental health by providing support and access to resources in a local community setting. With an aim to identify key elements that contribute toward enhancing the effectiveness of the Life Rooms social prescribing approach. Methods Data were obtained through six semi-structured focus groups with mental health service users from two locations in the North West of the UK. Postcode data was collected to generate an Index for Multiple Deprivation (IMD) score, to understand their socio-economic background. Data were analysed using thematic analysis. Results A total of 18 participants took part in the study. The majority of participants came from disadvantaged backgrounds; 14 participants measuring 3 and below in terms of overall IMD scores and 9 participants belonged to the poorest decile (IMD score = 1). Participants reported on different elements of the Life Rooms which they found as an effective approach to care. Four main themes emerged from the data: 1) social belonging: being able to just 'be' 2) resourceful and accessible; 3) social inclusion and connectedness; and 4) moving forward: self-development and independence. Conclusion Findings support the need and benefit social prescribing to improve mental health wellbeing and reduce the burden of mental illness.